Large-scale spatiotemporal variation in calf sex ratio in moose ( Alces alces ): an effect of density-dependent decrease in maternal condition? - Bjørneraas, K.; Solberg, E. J.; Herfindal, I.; Sæther, B.-E. (Canadian Journal of Zoology, 2009)
The harvest of Norwegian moose ( Alces alces (L., 1758)) is directed towards certain sex and age classes to maximize yield in terms of meat or number of animals. Observed side effects are declining numbers of calves per female and proportions of adult males, which may affect other demographic variables. Using long-term data, we examined whether spatiotemporal variation in the calf sex ratio was related to changes in (i) density of harvested moose, (ii) recruitment rate, and (or) (iii) the composition of the adult segment of the population. We found declining proportions of male calves in the autumn harvest over time associated with decreasing recruitment rates. Similarly, the proportion of male calves was lower when density of harvested moose was high. We suggest that the decrease in proportion of male calves was caused by increased prenatal or postnatal mortality rates of males, possibly owing to a density-dependent decline in maternal body condition. Proportion of male calves increased with the proportion of adult males in the population the previous year, indicating that low proportions of adult males may lead to lower male recruitment, particularly at high densities. Further declines in proportions of male calves recruited may be avoided by reducing the population density and changing the demographic composition of the harvest.